Factors contributing resistance to change in new organizational structure at "Majlis Daerah Segamat" / Mohd Izharul Hanif Adnan - Hanif Adnan, Mohd Izharul (Faculty of Business and Management, 2014)
This research entitles "FACTORS CONTRIBUTING RESISTANCE TO CHANGE IN NEW ORGANIZATIONAL STRUCTURE AT "MAJLIS DAERAH SEGAMAT". Therefore, the study is conducted to identify the relationship of factors that contribute to people resist changing towards organizational structure change at "Majlis Daerah Segamat". Firstly, to identify the relationship between fear of unknown and new organizational structure change that implemented at "Majlis Daerah Segamat". Second, to examine the relationship between loss of control and new organizational structure change that implemented at "Majlis Daerah Segamat". Third, to identify relationship between lack of confidence and new organizational structure change that implemented at "Majlis Daerah Segamat". Fourth, to find the relationship between fear of taking risk and new organizational structure change that implemented at "Majlis Daerah Segamat". Lastly, to identify how much those factors contributing toward resistance to change and new organizational structure that implemented at "Majlis Daerah Segamat". The study involved 100 staffs Internal Audit, Building and Engineering, Management Service, Corporate and Public Affairs, Finance, Law and Social Development at "Majlis Daerah Segamat". The questionnaires consists 30 questions that divided into three parts. Part A has 6 questions that consists the respondent's demographic background information which gender, age, race, marital status, education background and working experience. Part B have questions of factors resistance to change which are fear of unknown consists 4 questions, loss of control consists 5 questions, lack of confidence consists 5 questions and fear of taking risk consists of 5 questions. Part C has 5 questions on organizational structure.